Nugget Gemarikan (Steamed Rice Mixed with Additional of Mackerel) as an Alternative Food to Prevent Stunting - Candradewi, Anak Agung Istri; Ipa, Agustian; Asikin, Hijrah (LPPM Universitas Dhyana Pura, 2025)
Stunting remains a crucial public health issue in Indonesia. This condition of impaired growth is primarily triggered by chronic malnutrition, especially during the first 1,000 days of life (HPK). The impacts of stunting are irreversible on children's growth and cognitive development. Although the prevalence of stunting in Indonesia decreased to 21.6% in 2022, this figure is still far from the national target of 14% by 2024. One of the strategies to address stunting is through the provision of protein- rich supplementary foods, such as mackerel. This study aimed to design and modify a functional food product named